STUDY OF THE INFLUENCE OF CUTTING CONDITIONS ON CUTTING FORCES WHEN DRILLING ALUMINUM ALLOY - Kenjaboev Shukurjon Sharipovich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article describes the features of the processing of aluminum alloys, in particular, cutting, considers the process of this type of processing of aluminum alloys, and the influence of its cutting conditions on the quality of surfaces